TAPAK EKOLOGI KEPARIWISATAAN ALAM PADA ZONA PEMANFAATAN DI TAMAN NASIONAL GUNUNG MERAPI (TNGM) (Konsep Pengembangan Kepariwisataan Alam Tematik Tapak Kawasan Kalikuning-Kaliadem Sebagai Kawasan Budaya Vulkanik ) - Muhamad Muhamad (Universitas Gadjah Mada, 2017)
Merapi forest ecosystem has a very important ecological value for the Merapi region in particular and the districts (Sleman, Magelang, Boyolali, Klaten) in general. The ecosystem has given area function as a provider of environmental services and natural tourism, as a place of biodiversity, water catchment areas. Protected forests around Kalikuning-Kaliadem has tropical rainforest vegetation species are very specific. Objective assessment tread design of nature tourism at Merapi Mount can provide a reference to the zone setting function space utilization for the development of nature tourism. The method used in this research is the interpretation and assessment and see the diversity of tropical rain forest ecosystem and its interaction with topografi hill-slopes are capable of becoming a new destination in the development of ecological tourism. Interpretation can be packaged in the form of interpretation and information ecosystems located area in Kalikuning nature. The results showed that the protected forest that is Kalikuning-Kaliadem TNGM can be used as a development site volcanic areas of cultural, ecological, and the very high of community interaction rescuers around.